Aqueous humour cytokine changes during a loading phase of intravitreal ranibizumab or dexamethasone implant in diabetic macular oedema. Issue 4 (17th November 2019) - Podkowinski, Dominika; Orlowski‐Wimmer, Eva; Zlabinger, Gerhard; Pollreisz, Andreas; Mursch‐Edlmayr, Anna‐Sophie; Mariacher, Siegfried; Ring, Michael; Bolz, Matthias
Abstract: Purpose: To determine the effect of intravitreal ranibizumab and a dexamethasone implant on aqueous humour cytokine, protein and enzyme levels and to correlate findings to morphologic and functional changes. Methods: In a prospective, randomized, controlled, double‐blind study, patients with clinically significant diabetic macular oedema (CSME) were randomly allocated to receive either monthly intravitreal injections of ranibizumab (Lucentis, Novartis Pharma) or a single dexamethasone implant (Ozurdex, Pharm‐Allergan) at baseline (BL). Aqueous humour samples were collected at BL and weeks 2, 8 and 20. Results: The study included 18 eyes of 18 patients. In the dexamethasone implant group, soluble intercellular adhesion molecule 1 (sICAM‐1) (weeks 2 and 8), CXCL9/monokine induced by gamma interferon (MIG) (weeks 2 and 8), soluble vascular cell adhesion protein 1 (sVCAM‐1) (weeks 2 and 8) and monocyte chemo‐attractant protein 1 (MCP‐1) (week 2) levels were significantly decreased compared with baseline. In the ranibizumab group, placental growth factor (PIGF) (week 2) and vascular endothelial growth factor (VEGF) (week 2 and 8) levels were significantly decreased compared with baseline. No significant changes in central retinal thickness (CRT) or Early Treatment Diabetic Retinopathy Study (ETDRS) best corrected visual acuity (BCVA) were observed in the Ozurdex group at any time‐points. ETDRS scores significantly increased at week 20 (84.88 ± 8.88 letters) compared with baseline (74.78 ± 14.85 letters), and the CRT decreased significantly at week 4 (381.00 ± 114.64 μm) compared with baseline (440 ± 144 μm) in the Lucentis group. Conclusion: The dexamethasone implant affected the aqueous cytokines and proteins MCP‐1, sICAM‐1, sVCAM‐1 and MIG, whereas ranibizumab treatments reduced VEGF and PIGF levels. Morphological changes may diverge from cytokine changes. Results may indicate a rationale for a combination therapy for CSME using both agents, the dexamethasone implant and repeatedly administered ranibizumab injections.